PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KOMPETENSI DASAR MENDESKRIPSIKAN HUBUNGAN ANTARA KELANGKAAN-KELANGKAAN SUMBER DAYA DENGAN KEBUTU - Dassucik Dassucik; Riko Alambar (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
: Education is a form of manifestation of human culture is dynamic and full development . Because education has the task of preparing human resources for development . As a logical consequence , education is always faced with new problems . Problems facing the world of education is so broad , the first since the goal of human nature as a creature of mystery , both for educational efforts must anticipate the future to all its aspects that are not covered by the ability of human tellers . This study aims to determine whether to apply the method of Cooperative Learning Type Think Talk Write and activity can improve student learning outcomes . This research is Classroom Action Research ( CAR) conducted in Tanjung Selor Bulungan East Kalimantan . This study was done by researchers who acted as a teacher of Social Sciences. This study focused on Class VIII semester of academic year 2013/2014 , amounting to 28 students . The data collection method is a method of testing , observation and documentation . Based on the results of the study demonstrate that student learning outcomes are increased with 88.88 % of students who did not complete as many as four students in the subjects of Social Science in cycle 1 and 94.44 % with the students who did not complete as much as 2 students in Science subjects social in cycle 2 . While the student learning outcomes before the study is 83.33 % with a student who did not complete as many as six students in the subjects of Social Sciences meaningful improvement obtained with the implementation of Cooperative Learning Type Think Talk Write by 5.55 % in cycle 1 and cycle 2 for 11.11 % . Based on the results of this study concluded that the implementation of Cooperative Learning Type Think Talk Write quite effective and have experienced mastery learning both classical and individually. It can be seen from atusias students and students in the excitement of learning to follow the Social Sciences . This acquisition shows that the learning of Social Science in Class VIII semester of academic year 2013/2014 by using Cooperative Learning Type Think Talk Write effective enough to be applied.